Fabrication of cerium doped Ti/nanoTiO2/PbO2 electrode with improved electrocatalytic activity and its application in organic degradation. (20th May 2016) - Xu, Mai; Wang, Zhicheng; Wang, Fengwu; Hong, Ping; Wang, Canyong; Ouyang, Xuemei; Zhu, Chuangao; Wei, Yijun; Hun, Yunhu; Fang, Wenyan
Graphical abstract: Highlights: Novel Ti/Ce-nanoTiO2 /Ce-PbO2 electrodes are fabricated. This electrode possesses high electrochemical stability and electrocatalytic activity. High MO and COD removal efficiencies are achieved under optimized conditions. This electrode is promising anode as low-cost DSAs material for pollutants degradation. Abstract: In this work, the rare earth cerium (Ce) doped Ti/nanoTiO2 /PbO2 electrode (Ti/Ce-nanoTiO2 /Ce-PbO2 ) was successfully prepared using sol-gel and electrodeposition. It was found that the cerium doped nano TiO2 as underlayer could not only increase electrocatalytic property but could also withstand corrosion of the electrode. The surface morphology and the structure of the prepared thin film were characterized by scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS) and X-ray diffraction (XRD), respectively. SEM images indicated that the surface of Ti/Ce-nanoTiO2 /Ce-PbO2 electrode was more uniform and had smaller particles. Cyclic voltammetry (CV), linear sweep voltammetry (LSV) and electrochemical impedance spectroscopy (EIS) were also used to study electrocatalytic activity of electrodes. The large electrochemical active surface area and small charge transfer resistance resulted in the high electrocatalytic activity of Ti/Ce-nanoTiO2 /Ce-PbO2 . Electrocatalytic oxidation of methyl orange (MO) as a model dye wastewater in aqueous solution was studied to evaluate the potential applications of this electrode in environmental science. The chemical oxygen demand (COD) removal and average current efficiencies were about 96.6% and 14.6% for degrading 50 mg L −1  MO at a current density of 50 mA cm −2 and treatment time of 120 min. The good electrocatalytic performance of Ti/Ce-nanoTiO2 /Ce-PbO2 makes it a promising anode as low-cost dimensionally stable anodes (DSAs) for treatment of organic pollutants in aqueous solution.